Cowboys and indies : the epic history of the record industry - Murphy, Gareth (New York : Thomas Dunne Books, 2014)
From the invention of the earliest known sound-recording device in 1850s Paris to the CD crash and digital boom today, Murphy takes readers on an entertaining and encyclopedic ride through the many cataclysmic musical, cultural, and technological changes that shaped a century and a half of the industry.
Talking machines -- Judgments -- His master's voice -- Exodus -- The invisible wave -- Survivors -- Dead Sea crossing -- Homesick medicine -- Sunrise -- Lucky children -- Numbers -- The invasion -- Acts -- A slow eclipse -- Terra nova -- On black canvas -- Forbidden fruit -- Taurus -- Kings -- Psalms -- The island -- High tide -- Sources -- Sodom & Gomorrah -- Shadows -- Cyclops -- Legends -- Romans -- Lamentations -- Bubblegum forest -- Revelations.
Includes bibliographical references (pages 361-364) and index.
Keywords: Sound recording industry -- History